UWB Filtenna with Electronically Reconfigurable Band Notch using Defected Microstrip Structure - Ammar Alhegazi; Zahriladha Zakaria; Noor Azwan Shairi; Tole Sutikno; Sharif Ahmed (Institute of Advanced Engineering and Science, 2017)
A new design of filtenna with electronically reconfigurable band notch for ultra-wideband (UWB) applications is presented. The filtenna is designed based on modified monopole antenna integrated with resonant structure. To produce wider bandwidth with better return loss and higher frequency skirt selectivity, the monopole antenna is modified using microstrip transition in the feedline and block with a triangular-shape slot on each side of the circular patch. The resonant structure is about U-shaped slot defected on the feedline to achieve band notch characteristic. The position of the created band notch is controlled by optimizing the length of the U-shaped slot. By using a PIN diode switch inserted in the U-shaped slot to achieve reconfigurability feature. The experimental results show that the proposed design exhibits a wide bandwidth ranging from 3.0 to 14.0 GHz with reconfigurable band notch at 5.5 GHz (WLAN), and omnidirectional radiation pattern. Therefore, the proposed design is a good candidate for modern UWB applications.